The study of phospholipid bilayer of cell membranes in leukocytes incubated with high concentrations of the food additive E407a - Anton Tkachenko; Anatolii Onishchenko; Alexander Roshal; Yevgen Posokhov (National Scientific Medical Center, 2021)
The aim of the study was to assess the impact of semi-refined carrageenan (E407a) on the hydrophobic region of phospholipid bilayer in cell membranes of leukocytes exposed to the solution with high concentrations of this food additive. Materials and methods. Fluorescent probe (2-phenyl-phenanthro[9,10-d]-1,3-oxazole) was used to investigate the influence of E407a on the state of lipid bilayer in leukocytes extracted from rats and treated with a 5% solution of the food additive E407a during 4 hours.   Results. The shapes of the probe fluorescence spectra did not differ in leukocytes of rats treated with the 5% solution of semi-refined carrageenan and white blood cells of control samples. Such findings suggest that exposure to the E407a solution causes no changes in the proton-donor ability of the media in the lipid membranes of leukocytes in the region where the probe locates. Conclusion. Exposure of white blood cell suspensions to the semi-refined carrageenan solution does not affect the membrane hydration of the hydrophobic region of leukocyte phospholipid bilayer.